Role Of Dincharya As A Preventive Aspect Of Eye Disorder – A Review - Gupta, Ved Prakash; Marwah, Nitin; Bansal , Charu (International Research Journal of Ayurveda & Yoga, 2021)
In present era due to changing lifestyle particularly in the busy modern life and wrong posture during reading, writing, watching TV, office work on computer has resulted in many eye disorders like dry eye, computer vision syndrome, age related macular degeneration, glaucoma, cataract, diabetic retinopathy, hypertensive retinopathy, refractive error etc. There are five sense organs i.e. eye, ear, nose, tongue and skin. Among these sense organs, Ayurveda given prime importance to the Chakshurindriya (eye) and says “Sarvendriyaanam Nayanam Pradhanam”. Ayurveda aimed in prevention and cure of disease, Dinacharya is one of the concept which helps to fulfill this aim of Ayurveda. In Ayurveda text given various daily regimen like Anjana (collyrium), Padabhyanga (Foot Massage), Nasya (Nasal application of drugs), Snana (Bath), Netraprakshalna (eye wash), Netra Vyayamas (Eye exercise), Padaprakshalan (Cleaning foot) and Padatra Dharan (Use of footwear), Chhatra Dharan (Use of umbrella) for prevention of eye disease as well as maintenance and promotion of eye health. Now a day people do not follow these daily regimen due to busy schedule and lack of awareness which leads to Netra roga (Eye disorder). Hence the aim of this review article is to spread awareness about Dincharya for the maintenance of Eye health as well as prevention of eye disorder.